2017
DOI: 10.3390/nu9040362
|View full text |Cite
|
Sign up to set email alerts
|

Very Low Volume Sprint Interval Exercise Suppresses Subjective Appetite, Lowers Acylated Ghrelin, and Elevates GLP-1 in Overweight Individuals: A Pilot Study

Abstract: High-intensity exercise has been shown to elicit a transient suppression of appetite and create a more anorexigenic profile of appetite-associated hormones. It is yet to be fully elucidated whether such a response is observed following very low-volume, intermittent exercise at supramaximal intensity in those who are overweight. Eight overweight individuals (BMI 27.7 ± 1.7 kg·m2) completed resting (REST) and exercise (EX) trials in a counterbalanced order. EX consisted of 4 × 30 s “flat-out” cycling on an ergom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 42 publications
2
31
2
Order By: Relevance
“…In line with evidence in individuals who are lean, exercise-induced anorexia has been reported in studies recruiting individuals with overweight or obesity [57,58]. However, findings are inconsistent.…”
Section: Acute Exercisementioning
confidence: 73%
See 2 more Smart Citations
“…In line with evidence in individuals who are lean, exercise-induced anorexia has been reported in studies recruiting individuals with overweight or obesity [57,58]. However, findings are inconsistent.…”
Section: Acute Exercisementioning
confidence: 73%
“…Akin to studies in individuals who are lean, reductions in acylated ghrelin and elevations in PYY and GLP-1 have been reported concurrently with a suppression of appetite during exercise [57,58]. However, despite showing a reduction in acylated ghrelin in response to exercise, two studies found that moderate-and high-intensity cycling did not alter circulating PYY concentrations [59,60].…”
Section: Acute Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…() found that the energy‐intake was reduced for 2 days after the exercise session with highest peak intensity, this factor cannot completely explain the differential results. Lastly, it must be noted that other studies, carried out in nondiabetic subjects, have also found that exercise with higher peak intensity does not decrease (Holliday and Blannin ) and may even lead to higher energy‐intake than exercise with lower peak intensity (Pomerleau et al. ; Bilski et al.…”
Section: Discussionmentioning
confidence: 95%
“…These studies have both evaluated satiety and appetite-related hormones, but studies examining energyintake after exercise in subjects with T2D are lacking. This is important to assess since discrepancies between satiety and appetite-related hormones on one side and energyintake on the other have previously been reported (Bilski et al 2013;King et al 2013;Holliday and Blannin 2017).…”
Section: Introductionmentioning
confidence: 99%